2006
DOI: 10.2175/106143005x84495
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Wastewater Cations on Activated Sludge Characteristics: Effects of Aluminum and Iron in Floc

Abstract: Wastewater samples collected from seven wastewater treatment plants (WWTPs) were characterized to assess the impacts of wastewater cations on the activated sludge process. The cations included in this study were sodium (Na+), potassium, ammonium, calcium, magnesium, aluminum (Al), and iron (Fe). Among the selected cations, Al and Fe were of most interest to this study because their role in bioflocculation has not been extensively studied and remains largely unknown. The data showed that WWTPs contained highly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
49
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(58 citation statements)
references
References 32 publications
9
49
0
Order By: Relevance
“…Due to high charge density of Fe 3+ , the best flocculation ability (68% on average) was observed in the MBR-Fe. The previous investigations also supported this result that the trivalent cations showed considerable higher flocculating ability than bivalent or monovalent cations (Park et al, 2006;Li et al, 2012).…”
Section: Bioflocculation and Filterability Of Assupporting
confidence: 64%
See 1 more Smart Citation
“…Due to high charge density of Fe 3+ , the best flocculation ability (68% on average) was observed in the MBR-Fe. The previous investigations also supported this result that the trivalent cations showed considerable higher flocculating ability than bivalent or monovalent cations (Park et al, 2006;Li et al, 2012).…”
Section: Bioflocculation and Filterability Of Assupporting
confidence: 64%
“…Furthermore, it is generally accepted that polysaccharides (PS) and proteins (PN) are the major components of EPSs (Park et al, 2006). Since the sludge flocs possess a multilayered structure consisting of supernatant, slime, LB, TB, and pellet, the distribution pattern of PS and PN directly influence the AS characteristics (Yu et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, biochemical methane potential (B 0 ) was significantly improved by ZVI addition, indicating that ZVI increased the extent of sludge conversion and altered the sludge property 35 . It has been reported that VS destruction during anaerobic digestion of waste activated sludge generally increased with the increase of ferrous iron content in the sludge 36,37 . Indeed, ZVI can release from Fe 0 to Fe…”
Section: Resultsmentioning
confidence: 99%
“…Despite the lack of a clear understanding, sludge dewatering could be affected by a number of EPS-related parameters, such as floc size, structure, and bound water content (Liu and Fang, 2003). The increasing in bound EPS resulting from the addition of multivalent cations has been reported in numerous studies (Liu and Fang, 2003;Park et al, 2006), and the bound EPS showed improving sludge dewaterability (Higgins and Novak, 1997;Murthy and Novak, 1999). Though a better settleability was observed for Fe 2+ dosed sludge than Fe 3+ dosed one in this study, the sludge dewatering performance was not found affected by which Fe species was dosed.…”
Section: Sludge Dewaterabilitymentioning
confidence: 99%